2016
DOI: 10.1063/1.4945776
|View full text |Cite
|
Sign up to set email alerts
|

First-principle-based full-dispersion Monte Carlo simulation of the anisotropic phonon transport in the wurtzite GaN thin film

Abstract: In this study, we developed a first-principle-based full-dispersion Monte Carlo simulation method to study the anisotropic phonon transport in wurtzite GaN thin film. The input data of thermal properties in MC simulations were calculated based on the first-principle method. The anisotropy of thermal conductivity in bulk wurtzite GaN is found to be strengthened by isotopic scatterings and reduced temperature, and the anisotropy reaches 40.08% for natural bulk GaN at 100 K. With the GaN thin film thickness decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Several works have reported MC methods that incorporate a full phonon dispersion3031, however, these methods are computationally expensive as they do not employ the efficient algorithm of Peraud et al 2425…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have reported MC methods that incorporate a full phonon dispersion3031, however, these methods are computationally expensive as they do not employ the efficient algorithm of Peraud et al 2425…”
mentioning
confidence: 99%
“…Including the full phonon dispersion with the correct phonon density of states is essential to inferring key properties such as phonon transmission coefficients at the grain boundaries from experimental data 28 29 . Several works have reported MC methods that incorporate a full phonon dispersion 30 31 , however, these methods are computationally expensive as they do not employ the efficient algorithm of Peraud et al . 24 25 .…”
mentioning
confidence: 99%
“…The anisotropic thermal conductivity of -GaN recently attracted intensive attention because it is critical for heat management in power electronics, where -GaN is a key component. However, the answer remains controversial: some reported that the out-of-plane thermal conductivity is greater than the in-plane one while others showed opposite results [5,6,19,20] Recent reports suggest that the in-plane thermal conductivity is smaller than the out-of-plane one, with a relatively strong anisotropy of 12% [19,20]. Here, we will investigate the roles of phonon group velocity and scattering rates on the anisotropic lattice thermal conductivity.…”
Section: The Impact Of Matryoshka Phonon Twinning On the Anisotropic ...mentioning
confidence: 96%
“…For example, existing experimental measurements of the phonon dispersion relation of -GaN are limited to ambient conditions, and the phonon scattering processes and the temperature effects are mostly unexplored [9,10]. Moreover, the anisotropic thermal transport of -GaN along a (inplane) and c (out-of-plane) axis directions remains controversial due to the challenges in transport measurements [7,[11][12][13][14][15][16][17][18] and calculations [19][20][21]. Therefore, a more comprehensive understanding of the phonon dynamics is pivotal to investigating the thermal transport and other thermodynamics properties of GaN.…”
mentioning
confidence: 99%
“…Most later MC methods were derived from Peterson's work and extended its computational accuracy and geometric complexity [30][31][32][33][34][35][36][37]. Using realistic phonon spectra, the accuracy of the MC method can be improved significantly [38][39][40][41][42][43]. In particular, sophisticated nanostructures have attracted more interest for studying the effects of phonon ballistic transport [44,45] and interfacial scattering [46].…”
Section: Introductionmentioning
confidence: 99%